Determination of Competency, Work Discipline and Motivation on employee performance at Universities in Indonesia - Muhajirin, Adi; Ali, Hapzi; Widyastuti, Tri; Suroso, Sugeng (Journal of Accounting and Finance Management, 2024)
How to accept educational staff who lack competence with the level of job satisfaction of staff due to lack of competence and measure the level of motivation that has continued to decline since entering the staff, that the level of staff discipline has decreased. Quantitative research, which is a type of research emphasizing the testing of theoretical theories through measuring research variables with numbers and requiring data analysis with statistical procedures. The measuring instrument for this research is a questionnaire, the data obtained is in the form of answers from staff to the questions asked. based on the research objectives that have been set, this type of research is explanatory. The statistical t value of the effect of competence (KO) on motivation (MO) is 5.29 with a positive structural equation coefficient, that competence has a positive and significant effect on motivation. The more competence of university staff, it will increase employee motivation, otherwise the less competence the university staff has, it will reduce work motivation and can even transmit decreased motivation to other staff so that motivation becomes the main thing that must be owned by university staff. For universities, it is better when recruiting educational staff to have basic competencies so that they can increase the motivation of the staff themselves and form an academic culture that is in accordance with academic rules